2009
DOI: 10.1038/nature08677
|View full text |Cite
|
Sign up to set email alerts
|

E2f1–3 switch from activators in progenitor cells to repressors in differentiating cells

Abstract: In the classic paradigm of mammalian cell cycle control, Rb functions to restrict cells from entering S phase by sequestering E2F activators (E2f1, E2f2 and E2f3), which are invariably portrayed as the ultimate effectors of a transcriptional program that commit cells to enter and progress through S phase1, 2. Using a panel of tissue-specific cre-transgenic mice and conditional E2f alleles we examine the effects of E2f1, E2f2 and E2f3 triple deficiency in murine ES cells, embryos and small intestines. We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
216
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(237 citation statements)
references
References 31 publications
17
216
0
1
Order By: Relevance
“…Similar findings have been reported for differentiating monocyte and intestinal epithelial cells. 13,17 However, the cell fates in these cases are different from those observed in pancreatic tissue, as monocyte progenitor cells lacking E2F1/2 result in senescence, and intestinal progenitor cells lacking E2F1-3 lead to p53-independent apoptosis. The mechanism that leads to replication stress in DKO cells is still unknown, and it would be interesting to determine whether it involves illegitimate replication origin firing and fork stalling, as shown for replication stress caused by overexpression of Cdt1 33 or by aberrant CDK activity 34 in some cell types.…”
Section: E2f-p53 Regulatory Axis In Tissue Homeostasismentioning
confidence: 99%
See 2 more Smart Citations
“…Similar findings have been reported for differentiating monocyte and intestinal epithelial cells. 13,17 However, the cell fates in these cases are different from those observed in pancreatic tissue, as monocyte progenitor cells lacking E2F1/2 result in senescence, and intestinal progenitor cells lacking E2F1-3 lead to p53-independent apoptosis. The mechanism that leads to replication stress in DKO cells is still unknown, and it would be interesting to determine whether it involves illegitimate replication origin firing and fork stalling, as shown for replication stress caused by overexpression of Cdt1 33 or by aberrant CDK activity 34 in some cell types.…”
Section: E2f-p53 Regulatory Axis In Tissue Homeostasismentioning
confidence: 99%
“…[8][9][10] E2F1 and E2F2 are known to function both as transcriptional activators and as repressors of their target genes, including those coding for microRNAs. [11][12][13][14][15] Moreover, E2F1 and E2F2 perform positive as well as negative regulatory roles in cellular proliferation, which appear to be cell specific and context dependent. They have been reported to promote cellcycle entry and progression upon their ectopic expression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been recently shown that E2F1-3 are dispensable for proliferation, but necessary for cell survival in normally dividing progenitor cells. By contrast, they function as repressors in non-proliferating cells that are undergoing differentiation (Chong et al, 2009). However, the relative contribution of E2F1-3 in cell survival or in repression has not been determined for cellular contexts where terminal differentiation is not coupled to cell cycle exit, but is instead concurrent with continued proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, apoptotic induction of E2F1 separates it from other E2F family members [17]. In response to various DNA-damage conditions, including ionizing radiation, UV radiation and chemotherapeutic drugs, E2F1 is induced and activated, resulting in expression of its downstream genes for induction of cell apoptosis [18,19]. Notably, upon DNA damage, E2F1 undergoes post-translational modifications, including phosphorylation, acetylation and deacetylation, resulting in modulation of its transactivation [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%